Selected aspects of health behaviors among junior high school students - Kurzeja, Piotr; Prusak, Jarosław; Miśkowiec, Małgorzata; Szurmik, Tomasz; Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2019)
Introduction and purpose of the work: In the adolescent period, decisions made have a large influence on your future life. This applies, inter alia, to health behaviors that are also shaped during this period and may have an impact on further life. That is why it is so important for young people to take on good eating habits as well as lifestyle. The aim of the work was to learn about selected aspects of health behaviors in junior high school youth from rural and urban environments. Material and method: The study covered 98 students attending the 3rd grade of junior high school. The research was carried out in January 2017 using the form of the author’s questionnaire as a research tool. The results were analyzed statistically, using Microsoft Office Excel 2010 and the IBM SPSS Statistics program. Results: Among the junior high school students, the majority think that physical activity is the most important in a healthy lifestyle. The most common types of physical activity among junior high school students are volleyball, cycling, running, football. The most frequently indicated ways of spending free time are: using the Internet, meeting friends, active rest, reading books, watching TV. Conclusions: Both junior high school students from the city and the village show knowledge about health behaviors, especially when it comes to physical activity and healthy eating but a large number of respondents do not eat meals at fixed times, sleep is also neglected. Among junior high school students from the city, there was a greater tendency to display adverse health behaviors - addictions, than in the village ones. There is a need to constantly disseminate pro-health education and to shape correct attitudes and behaviors of young people.